File security using Advanced Encryption Standard and Least Significant Bit - Lykke, Felicia; Andreas Edvard; Feri Saputra (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Computer technology of rapid development has triggered crimes that take advantage of weaknesses in computer systems. One form of crime was the act of hackers who take data and information through computer security holes. The data was used for various things that are not appropriate. Information sent via communication media can be taken and misused by irresponsible parties. An electronic data security system has been developed. With the emergence of various data security methods such as encryption and steganography. Encryption was a way of securing data files by randomizing a document, while Steganography was securing electronic data by hiding a file within another file. Based on the feasibility test of the system with a questionnaire by 20 respondents, the result of 87%, which is categorized as "very good".